Relationship Analysis of Spiritual Intelligence with Life Satisfaction of College Students - Gill, Suman; Sharma, Seema; Kang, Tejpreet K. (International Journal of Economic Plants, 2023)
The present study was conducted during December-January, 2022–23 at Ludhiana, Punjab, India to assess the relationship between spiritual intelligence and life satisfaction among college students. The sample consisted of 220 college students aged between 23–24 years. The sample consisted of equal number of male (n=110) and female (n=110) students. Random sampling was done to draw sample from four colleges of district Ludhiana. The objective of the study was to assess the relationship between spiritual intelligence and life satisfaction of college students. Sixfold spiritual intelligence scale by Kaur (2017) and Life satisfaction scale by Singh and Joseph (2015) were used as data collection tools to assess the spiritual intelligence and life satisfaction of college students. Gender wise mean score differences among college students across different dimensions of spiritual intelligence revealed no significant differences among various dimensions. Gender wise mean score differences among college students across different levels of life satisfaction showed a significant difference at low level of life satisfaction. The results revealed that all the dimensions of spiritual intelligence were positively related to life satisfaction of male and female college students. It would be also helpful for parents, counsellors, psychologists and human development professionals to understand the level of spiritual intelligence of college students. The present study will be useful for the youth to understand the importance of spiritual intelligence and its relationship with life satisfaction.